GAMBARAN MOTIVASI BERPRESTASI SISWA KELAS VIII MTs ALBIDAYAH - Hartati .; Wahyu Hidayat; Devy Sekar Ayu Ningrum (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
The purpose of this study is to find out the picture of the motivation of achievement students of class VIII MTs Al Bidayah.The method used in this study is a quantitative approach with this type of quantitative deriftive research. The data collection method used in this study is a questionnaire that is adjusted from the indicators of Mc Clleland's achievement motivation theory (1961). The results showed that the achievement motivation of MTs. Albidayah students belonged to the high category with an average score (mean) of 86.3 and a percentage of achievement of 86.3%. The three dimensions of student motivation also showed high results, namely N-ach (mean = 57.37; achievement = 88.26%), N-aff (mean = 16.43; achievement = 82.17%), and N-pow (mean = 13.13; achievement = 87.56%). This means that students have a good enough motivation to perform when participating in learning activities in school. Keywords: : motivation, achievement, students